Exploring the role of library managers in supporting female professionals: Perspectives from Punjab Pakistan - Qurat Ul Ain Saleem; Kanwal Ameen (Malaysian Journal of Library and Information Science, 2024)
The primary aim of this study was to explore the role of immediate managers in fostering a congenial workplace environment for female library professionals. This research is based on qualitative data collected through semi-structured interviews with female library professionals employed in universities recognised by the Higher Education Commission in Punjab, Pakistan. The findings revealed that most managers offer constructive feedback to their subordinates, which the participants noted had a positive impact, enhancing both efficiency and work performance. They also reported that their managers encouraged female employees to share their opinions and introduce new ideas. Furthermore, the study elaborated on the participants’ suggestions to help managers improve the congeniality of the workplace environment. These findings are valuable for raising awareness among management and authorities regarding the expectations of subordinates from their managers. Additionally, the results can inform the development of policies aimed at creating a healthy and productive work environment that benefits both employees and the organisation.